Pemetaan Status Gizi Balita di Indonesia - Alinea Dwi Elisanti (Universitas Muhammadiyah Ponorogo, 2017)
The health status of children under five is one of the primary indicators of public health in a country. Nutritional became one of the health problems that affect the quality of human resources, an indicator of the success of the nation's development and could result in infant mortality and morbidity. Some research suggests that social and demographic conditions affecting the nutritional status of children, factors or geographic region will be very important role in the incidence of nutritional problems in Indonesia. So the need for mapping the problem to determine troubleshooting steps. This study aims to map the nutritional status of children under five in Indonesia. The method used is non-reactive studies using secondary data reports Riskesdas 2010. The sample taken is the entire province in Indonesia. Data were analyzed using ArchView GIS 3.3. The results showed that there are three (3) of the province that has the most low nutritional status of children in Indonesia, East Nusa Tenggara (NTT), Southeast Sulawesi and North Maluku. The provinces that have good nutritional status (height), the DI Yogyakarta, Jakarta and West Sumatra.